Attitude, Aptitude, Routines, Pattern, Dan Simple Codes Dalam Pemerolehan Bahasa - Rizki Amalia Sholihah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
In the study of language, which required a learner not just aptitude (language intelligence) but the main thing is more attitude are accompanied by a strong motivation and purpose that would make a learner managed to learn the language. The routine of the first language often provide positive influence against the routine that is studied in a second language. However this happens if there are routines from both the language experienced a resemblance. For the first pattern language, often give bad influence, due to the difference in the pattern of the first language with the pattern of a second language. In addition, in communicating, sometimes language learners experience difficulties when will convey something he has yet to figure out the language in the second language. Then use simple codes will help learners understand what is to be delivered.